Applied plant biotechnology for improving resistance to biotic stress - Poltronieri, Palmiro; Hong, Yiguo (Academic Press, 2019)
Applied Plant Biotechnology for Improvement of Resistance to Biotic Stress applies biotechnology insights that seek to improve plant genomes, thus helping them achieve higher resistance and optimal hormone signaling to increase crop yield. The book provides an analysis of the current state-of-the-art in plant biotechnology as applied to improving resistance to biotic stress. In recent years, significant progress has been made towards understanding the interplay between plants and their hosts, particularly the role of plant immunity in regulating, attenuating or neutralizing invading pathogens. As a result, there is a great need to integrate these insights with methods from biotechnology. --